Demonstrating the potential of amberat middens for understanding late Quaternary palaeoenvironments in the Central Pilbara, western Australia. (10th October 2022) - McBride, Emily; Wallis, Lynley A.; Hopf, Felicitas; Haberle, Simon G.; Dardengo, Mia
Abstract: The Pilbara region in Western Australia (WA) is of high biological and archaeological significance, though our understanding of its environmental history is limited. Potentially valuable palaeoenvironmental archives exist throughout the Central Pilbara in caves and rockshelters in the form of amberat middens (crystallised animal urine), which are known from elsewhere to preserve botanical and faunal remains. Here we report a pilot study aimed at assessing how a multiproxy analysis of these middens could be used to infer past environmental change in response to climate change and therefore help to characterise the nature of past human-environmental relationships in the Pilbara region. Findings show that rockshelters of the inland Pilbara contain some of the oldest known amberat middens in Australia, extending fully back to the Last Glacial Maximum (LGM). Well preserved pollen and macrofossils in the middens tentatively suggest that vegetation throughout the late Pleistocene was likely dominated by an open woodland with a shift after 6000 BP to a more heterogenous pattern of vegetation with the increasing dominance of grassland communities. Several hiatuses in midden accumulation are apparent, which are tentatively interpreted as indicating that the region was affected by prolonged dry periods in the past. This may help explain concomitant patterns of decreased human occupation in the corresponding archaeological record. This pilot study has demonstrated the value of amberat middens for providing much needed local paleoenvironmental data in arid and semi-arid regions of Australia.